Preparation of cigarette butts/coal‐based porous carbon and its catalytic methane decomposition to hydrogen. Issue 2 (14th December 2020) - Luo, Huafeng; Li, Tongda; Qiao, Yuandong; Ning, Zhangxuan; Bo, Chunli
Abstract: A new type of cigarette butts/coal‐based composite porous carbon was prepared by potassium hydroxide chemical activation method and used for methane decomposition to hydrogen. The effects of mass mixing ratio of the used cigarette butts/coal and carbonization temperature on the surface properties and structure of carbon materials were studied. The results show that the optimal mass mixing ratio of cigarette butts/coal is 1:3, and the increase in temperature can promote the specific surface area of carbon materials from 1850 to 2785 m 2 /g, the distribution of pore size is also changed from a large number of micropores to mesopores, and the structure became more disordered. DT/YT‐3‐1023 has the highest initial activity, DT/YT‐3‐1123 has the highest stability, and a certain amount of carbon fibers are deposited on the surface of carbon materials after the reaction.